Angular distribution of cross-sectioned cell boundaries at the distal terminal web in differentiating preameloblasts, inner enamel secretory ameloblasts and outer enamel secretory ameloblasts. (27th November 2013) - Yuan, Xiaohong; Nishikawa, Sumio
Abstract: The cross-sectioned profiles of differentiating preameloblasts, inner enamel secretory ameloblasts and outer enamel secretory ameloblasts at the distal terminal web were quantitatively compared. First, the angles of each line constituting the sectioned cell polygons were measured, and the patterns of angular distribution histograms were compared. Second, all groups of line angles from one differentiating preameloblast population, two inner enamel secretory ameloblast and one outer enamel secretory ameloblast populations at the distal terminal web were compared statistically by the χ 2 -test using the multiple comparison method. The results showed that cell shapes between differentiating preameloblasts and inner enamel secretory ameloblasts were similar, but that those between differentiating preameloblasts and outer enamel secretory ameloblasts and between inner enamel secretory ameloblasts and outer enamel secretory ameloblasts were significantly different. Third, F-actin fluorescence microscopy in the distal terminal web was performed and was consistent with the angular distribution. These results suggest that cell shapes of inner enamel secretory ameloblasts and differentiating preameloblasts at the distal terminal web are specialized for sideways cell movement during decussating tooth enamel formation.